Solar Irrigation for Agricultural Resilience (SoLAR) in South Asia: impact pathways - International Water Management Institute (International Water Management Institute, 2025)
The Solar Irrigation for Agricultural Resilience (SoLAR) program, led by the International Water Management Institute (IWMI) with support from the Swiss Agency for Development and Cooperation (SDC), has advanced climate-resilient, gender-equitable, and socially inclusive farming livelihoods in Bangladesh, India, Nepal, and Pakistan since 2019. By promoting solar irrigation pumps (SIPs), the initiative supports clean energy transitions in agriculture, reducing reliance on diesel and helping farmers adapt to rainfall variability without significantly increasing groundwater use. Key learnings from the program emphasize four pillars for sustainable transitions: robust evidence for policy, diverse and scalable business models, inclusive policy advocacy, and strengthened gender and social inclusion through community engagement and capacity building. Beyond South Asia, SoLAR is fostering South-South collaboration to extend these lessons to East Africa, contributing to global pathways for sustainable and inclusive agricultural resilience.